2020
DOI: 10.1186/s12870-020-02406-3
|View full text |Cite
|
Sign up to set email alerts
|

The sucrose transporter MdSUT4.1 participates in the regulation of fruit sugar accumulation in apple

Abstract: Background: Sugar content is an important determinant of fruit sweetness, but details on the complex molecular mechanism underlying fruit sugar accumulation remain scarce. Here, we report the role of sucrose transporter (SUT) family in regulating fruit sugar accumulation in apple. Results: Gene-tagged markers were developed to conduct candidate gene-based association study, and an SUT4 member MdSUT4.1 was found to be significantly associated with fruit sugar accumulation. MdSUT4.1 encodes a tonoplast localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 83 publications
(115 reference statements)
0
23
0
Order By: Relevance
“…Indeed, HXK1 can form a complex with a vacuolar H + -ATPase and the 19S subunit of the proteasome, that directly modulates the expression of target genes ( Cho et al., 2006 ). While most SUT transporters are localized in plasma membrane, some members of SUTII subfamily were found associated with vacuole membrane and their overexpression results in increased sucrose accumulation in this organelle ( Ma et al., 2017 ; Ma et al., 2019 ; Peng et al., 2020 ). Surprisingly, a negative correlation between apple tonoplast MdSut4.1 expression and sucrose accumulation was observed, and was confirmed by transient overexpression in strawberry fruit, suggesting a function in sucrose remobilization out of the vacuole ( Schneider et al., 2012 ; Peng et al., 2020 ).…”
Section: Sugar Signaling In Fruit Development and Ripening And Its Crmentioning
confidence: 99%
“…Indeed, HXK1 can form a complex with a vacuolar H + -ATPase and the 19S subunit of the proteasome, that directly modulates the expression of target genes ( Cho et al., 2006 ). While most SUT transporters are localized in plasma membrane, some members of SUTII subfamily were found associated with vacuole membrane and their overexpression results in increased sucrose accumulation in this organelle ( Ma et al., 2017 ; Ma et al., 2019 ; Peng et al., 2020 ). Surprisingly, a negative correlation between apple tonoplast MdSut4.1 expression and sucrose accumulation was observed, and was confirmed by transient overexpression in strawberry fruit, suggesting a function in sucrose remobilization out of the vacuole ( Schneider et al., 2012 ; Peng et al., 2020 ).…”
Section: Sugar Signaling In Fruit Development and Ripening And Its Crmentioning
confidence: 99%
“…In recent years, studies on many horticultural plants have demonstrated that sugar accumulation is closely related to sucrose transporters and sucrose metabolism enzymes. An apple sucrose transporter MdSUT4 was found to be signi cantly associated with fruit sugar accumulation (Peng et al 2020). Sucrose synthase may play a critical role in the sugar metabolism of sucrose-accumulating grape berries (Shiraishi and Hamada 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In apples, the expression of members of the sugar transporters family (e.g. SUT2 and SUT4 genes) facilitate sugar accumulation via the apoplastic pathway [ 65 ]. In kiwi fruits, high numbers of PD were observed in the SE-CC interface but not in the post-phloem unloading domains (CC-PC or SE-PC) concomitant with restricted symplasmic unloading of CF [ 54 ].…”
Section: Phloem Unloading Pathways In Developing Fruits: a Role For Pdmentioning
confidence: 99%